Algorithmic Literacy, Digital Literacy, and Perceived Digital Self-Efficacy as Predictors of Social Media Engagement Among Filipino Emerging Adults in the City of Manila - Maria Alexandra C. Odvina; Renee Maxine S. Lazaro; Yashas N. Sah; Edmond Jacob C. Sy; Andrew C. Lim Un; Myla M. Arcinas (Future Science / FSH-PH Publications, 2026)
The rapid spread of recommender algorithms has made the competencies that govern how young people interpret and act in digital spaces a pressing concern. This study examined levels of algorithmic and digital literacy, as well as perceived digital self-efficacy, among Filipino emerging adults and tested whether these competencies predicted their social media engagement. Using a descriptive-correlational and predictive design, a researcher-adapted survey was administered through non-probability sampling to 77 eligible emerging adults from the City of Manila. Given the non-probability sampling and ordinal data, levels were summarized using the median (Mdn) and interquartile range; associations were tested with Spearman’s rank-order correlation; and predictors were identified through median (quantile) regression. Respondents showed a very high level of algorithmic literacy (Mdn = 4.50) and high levels of digital literacy (Mdn = 4.11), perceived digital self-efficacy (Mdn = 4.20), and social media engagement (Mdn = 3.83). All three competencies were significantly and positively associated with engagement: algorithmic literacy (ρ = .30, p = .003), digital literacy (ρ = .39), and perceived digital self-efficacy (ρ = .41), the latter two at p < .001. In the median regression, however, digital literacy was the only significant unique predictor of engagement (b = 0.47, p = .003); perceived digital self-efficacy and algorithmic literacy did not contribute uniquely once digital literacy was accounted for. Practical digital competence, rather than algorithm awareness or digital confidence alone, appears to most directly account for how emerging adults engage online, underscoring the value of competency-based digital citizenship programs.